The comparative study of antigenic protein characters of field isolates Brucella abortus cells with electrophoresis and immunoblotting Techniques - Sudibyo, Agus; Pasaribu, Facriyan H; Wibawan, I.W.T.; Setiawan, Endhie (Indonesian Journal of Animal and Veterinary Sciences, 1995)
Live vaccine of Brucella abortus strain 19 has been used for prevention and eradication of brucellosis in cattle . The information of the use of this vaccine in Indonesia is still limited, while the effectivity, bacteriological and serological aspects of the vaccine are not much evaluated yet. The objective of this research is to study the differences of protein cell wall antigenicity profiles between B. abortus strain 19, strain 544 and field isolates. Protein cell wall was prepared by sonicafion of B. abortus S19, S544 and B. abortus field isolates biotype l, 2 and 3 . Antiserum against these B. abortus was prepared in cattle . Futhermore, the distribution of protein band was determined by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), while protein antigenic profiles was examined by immunoblotting . The result showed that there was no significant different amongs protein cell wall of these B. abortus. From the antigenicity profiles exhibited that cattle vaccinated with B. abortus S19, no antibody was detected against protein less than 30 kDa. The other side natural infected or experimental infected cattle with B. abortus biotype 1 field isolate, antibody was detected until protein which has molecular weight about 15 kDa. Key words: Brucella abortus, antigenic protein, immunoblotting